2011
DOI: 10.1016/j.jhep.2011.02.010
|View full text |Cite
|
Sign up to set email alerts
|

A diagnostic approach to hyperferritinemia with a non-elevated transferrin saturation

Abstract: Elevated serum ferritin concentrations are common in clinical practice. In this review, we provide an approach to interpreting the serum ferritin elevation in relationship to other clinical parameters including the patient history, transferrin saturation, serum concentrations of alanine, and aspartate aminotransferases (ALT, AST), testing for HFE mutations, liver imaging, liver biopsy, and liver iron concentration. We used observations from a large series of patients with hepatic iron overload documented by li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0
16

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(111 citation statements)
references
References 32 publications
3
92
0
16
Order By: Relevance
“…Generally, the patient had high serum ferritin with metabolic syndrome without iron overload (obesity, type 2 diabetes mellitus, hypertriglyceridemia and hypertension) [1,16,17].…”
Section: Case Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Generally, the patient had high serum ferritin with metabolic syndrome without iron overload (obesity, type 2 diabetes mellitus, hypertriglyceridemia and hypertension) [1,16,17].…”
Section: Case Discussionmentioning
confidence: 98%
“…The remainder 5-15% is found in the iron transport protein transferrin, as well as in myoglobin, cytochromes and as unbound serum iron [1]. Elevated Serum Ferritin (SF) is commonly encountered in primary care.…”
Section: Case Study Introductionmentioning
confidence: 99%
“…Chandok et al 15 studied 482 patients, but only 108 of these subjects underwent histological or radiological investigation and had liver abnormalities compatible with NAFLD. They found that AST/ALT ratio, DM, splenomegaly and age were predictors of the NAFLD stage.…”
Section: Analysis Of Selected Articlesmentioning
confidence: 99%
“…Forbigående økning ses ved akutt inflammatorisk sykdom med økt syntese av ferritin og andre akuttfaseproteiner, og ved tilstander som gir levercelleskade med lekkasje av ferritin, saelig hepatitt og sporadisk overdrevet inntak av alkohol (2). Varig hyperferritinemi ses ved kroniske tilstander som alkoholisme, infeksjon, inflammatorisk sykdom, fettlever, diabetes, enkelte kreftsykdommer, hemolyse og jernoverskudd på grunn av arvelig hemokromatose (1,3).…”
Section: G/ 100 Ml) Han Hadde Vaert Blodgiver Og Gitt Blod Sju Gangeunclassified